Decision Analysis of the Use of Ex-Termination Materials for Operating Cost Efficiency with a Multi-Criteria Approach in an Indonesian Upstream Oil and Gas Company - Tri Haryanto; Niniet Indah Arvitrida (Journal of World Science, 2025)
This study aims to develop a more effective and data-based strategy for the management of ex-termination materials in the upstream oil and gas industry, integrating ABC, VED, and FMSD methods with Analytical Hierarchy Process (AHP). The analysis was carried out by integrating the ABC-FMSD-VED matrix approach. The results showed that 21% of category A materials accounted for 80% of the total inventory value, while 85.95% of materials were included in the Deadstock category, which was not optimally utilized. The AHP analysis showed that the top priority was internal utilization, followed by borrowing, transfer, and deletion, with sensitivity tests indicating decision stability.